Spinal stabilization of pathological fractures in metastatic disease in distant segments - a case report: Spinal stabilization of pathological fractures - Stojadinović, Ivan; Milošević, Jelena; Vlajović, Srđan; Jovanović, Zoran; Prodanović, Nikola; Todorović, Dušan (Medicinski časopis, 2021)
Introduce: About 2/3 of malignant tumors develop metastases. The skeletal system is the third most common site of metastasis, of which the spine is in the first place in terms of prevalence. Skeletal metastases can occur in all types of malignant tumors, and the breast is one of the most common localizations. Treatment of vertebral fractures can be non-operative and operative. Although numerous studies show the benefit of both non-operative and operative treatment, depending on the situation, several of them recommend a surgical approach as a better way to preserve patient mobility. Case report: The patient contacted a spinal surgeon due to back pain, when she was diagnosed with a pathological fracture of the 7th cervical and 12th thoracic vertebrae. Both fractures were operatively treated, in two time intervals. Discussion and conclusion: Given the advances in the treatment of malignant diseases, more people with spinal metastases live today than ever before in history. Patients with unstable pathological fractures are treated surgically, while patients who have stable fractures without dislocation can be treated only with chemotherapy and radiotherapy. The presentation of this patient showed how pathologically unstable vertebral fractures were treated on several levels. Operational approaches were as different as operational techniques. After surgical treatment and early rehabilitation, there was a significant improvement in the clinical picture and quality of life of the patient.